Turmeric (Curcuma longa) Extract Characterization for Corrosion Inhibitor using Microwave-Assisted Extraction - Tifa Paramitha; Angely Luviana; Angelina Putri; Randi Reynaldi; Rafila Chika Azzahra; Tika Paramitha; Rony Pasonang Sihombing (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2024)
Metallic corrosion, the deterioration process induced by the interaction between metals and corrosive environments, poses a significant challenge to material integrity and longevity. Corrosion inhibitors have been identified as an effective approach among various mitigation strategies. Natural extracts, such as those derived from turmeric/Curcuma longa, have garnered attention for their potential as eco-friendly corrosion inhibitors. This study endeavors to extract, characterize, and evaluate turmeric extract's efficacy as a corrosion inhibitor within a 30% acetic acid solution. Employing microwave-assisted extraction with a 96% ethanol solvent facilitated the isolation of the extract, which was subsequently subjected to qualitative analysis through phytochemical screenings and Gas Chromatography-Mass Spectrometry (GC-MS). These analyses confirmed the presence of antioxidative phytochemicals, including alkaloids, terpenoids, turmeronoids, curcumin, sesquiterpenoids, and phenols. The corrosion inhibitory properties of turmeric extract were assessed via immersion and flow loop experiments, revealing a notable reduction in corrosion rates—from 0.1540 mm/year to 0.0801 mm/year in immersion tests and from 5.3747 mm/year to 2.9369 mm/year in flow loop tests. Such outcomes underscore turmeric extract's potential as a viable corrosion inhibitor, attributed primarily to the chemical interactions facilitated by curcumin's phenolic and carbonyl groups with the metal surface, thereby enhancing protective efficacy. The inhibitor efficiency was quantified at 47.9743% and 45.3565% for immersion and flow loop tests, highlighting the extract's substantial inhibitory performance.